An Approach to the Bicyclic C‐5–C‐17/C‐19–C‐20 (BC) Portion of Neoclerodane Diterpenes by Intramolecular Diels–Alder Reaction1. Issue 19 (8th May 2014) - Wang, Yuzhou; Rogachev, Victor; Wolter, Martin; Gruner, Margit; Jäger, Anne; Metz, Peter
Abstract: Using a highly diastereoselective intramolecular acrylate [4+2] cycloaddition as the key step, a short route from 3‐furaldehyde to a bicyclic building block for the synthesis of neoclerodane diterpenes was developed. A first attempt featuring a conjugate methylation of a dienyl lactone failed, but a streamlined sequence using an all‐encompassing intramolecular Diels–Alder reaction of a sterically congested 1, 3‐diene was successful. Abstract : A highly diastereoselective intramolecular acrylate [4+2] cycloaddition of a sterically congested 1, 3‐diene served as the key step in a short synthesis of a BC building block for neoclerodane diterpenes.